Inflammation-induced ROS generation causes pancreatic cell death through modulation of Nrf2/NF-κB and SAPK/JNK pathway. (2nd November 2015) - Choudhury, S.; Ghosh, S.; Gupta, P.; Mukherjee, S.; Chattopadhyay, S.
Abstract: Chronic pancreatitis is characterized by progressive loss of exocrine and endocrine functions of the pancreas and is considered to be the single most important cause for development of pancreatic cancer. Recent evidence suggests that inflammation and oxidative stress play pivotal roles in the development of clinical conditions like pancreatitis, type 2 diabetes mellitus, and metabolic syndrome. Nonetheless, molecular signaling pathways linking inflammation, oxidative stress, and pancreatic cell death are not yet well defined. In this study, bacterial lipopolysaccharide (LPS) was used (injected twice a week for three weeks) to emulate a chronic systemic inflammatory state in experimental Swiss albino mice. Using this model, we traced the genesis of inflammation-induced pancreatic dysfunction and mapped the signaling events which contribute to the induction of this state. Histopathological studies revealed the appearance of cell injuries and increased collagen content in LPS-exposed group, indicative of fibrosis. Assays for intraperitoneal glucose tolerance, insulin levels, and insulin receptor mRNA expression signified inflammation-induced insulin insensitivity. For the first time we present evidence that cellular inflammation and subsequent oxidative stress modulate the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)/NF-E2-related factor 2 or Nuclear factor (erythroid-derived 2)-like 2 pathway and initiates pancreatic cell death by activation of stress-responsive Rho/stress-activated protein kinase or SAPK/Jun-N-terminal kinase (JNK) pathway. Scavenging of intracellular reactive oxygen species (ROS) by a standard antioxidant N-acetyl cysteine led to pancreatic cell survival. The data obtained strongly indicates that the LPS/toll-like receptor-4 or TLR-4/ROS/NF-κB pathway is critically involved in the initiation of inflammation, oxidative stress, and pancreatic cell death and might prove to be an excellent choice as a target for novel therapeutic strategies in the management of metabolic disorders.